2021
DOI: 10.3389/fnins.2020.629572
|View full text |Cite
|
Sign up to set email alerts
|

An Inter- and Intra-Subject Transfer Calibration Scheme for Improving Feedback Performance of Sensorimotor Rhythm-Based BCI Rehabilitation

Abstract: The Brain Computer Interface (BCI) system is a typical neurophysiological application which helps paralyzed patients with human-machine communication. Stroke patients with motor disabilities are able to perform BCI tasks for clinical rehabilitation. This paper proposes an effective scheme of transfer calibration for BCI rehabilitation. The inter- and intra-subject transfer learning approaches can improve the low-precision classification performance for experimental feedback. The results imply that the systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Then, the regularization parameter calculated using the divergences of all source subjects is added to the objective function of logistic regression classifier to make full use of the labeled samples from the source subjects correctly. Cao et al (2021) verified the applicability of wLRTL approach for stroke patients and intra/inter- subjective conditions.…”
Section: Transfer Learningmentioning
confidence: 54%
“…Then, the regularization parameter calculated using the divergences of all source subjects is added to the objective function of logistic regression classifier to make full use of the labeled samples from the source subjects correctly. Cao et al (2021) verified the applicability of wLRTL approach for stroke patients and intra/inter- subjective conditions.…”
Section: Transfer Learningmentioning
confidence: 54%
“…Moreover, in 2020, we confirmed the clinical efficacy of BCI training on stroke patients with upper limb dysfunction in both sub-acute and chronic stages, and we explored the closed-loop brain activation changes in sensorimotor rhythm (Chen et al, 2020a;Miao et al, 2020). In 2021, we proposed an inter-and intra-subject transfer calibration scheme for improving feedback performance of the closed-loop BCI training (Cao et al, 2020). In the same year, we compared the differences between motor attempt and motor imagery tasks, which are commonly used in a closed-loop BCI system (Chen et al, 2021).…”
Section: Introduction Concept and Development Of The Theory Of Centra...mentioning
confidence: 84%
“…The number of studies exploring transfer learning using stroke data is limited. Cao et al proposed a scheme to conduct transfer calibration based on the performance of existing methods [55]. They evaluated intra-and inter-subject transfer learning calibrations using data from seven stroke patients and found that their scheme benefitted low-precision sessions the most.…”
Section: Transfer Learning In Stroke Patientsmentioning
confidence: 99%